ROH HIZBUT TAHRIR DI BUMI PANCASILA - Arthur Aritonang (STT Bethel The Way, 2020)
This article examines the HTI organization whose ambition is to realize the caliphate system in Pancasila land. The existence of HTI is ideologically and practically very destructive of the spirit of the identity of the Indonesian nation as a state with schemes. The existence of the HTI organization raises concerns for the future of a pluralistic Indonesian nation. During the Reformation era, HT / Hizbut Tahrir's activities turned into an organization that received legal legitimacy from the Government so that the Hizbut Tahrir Indonesia organization was formed. The purpose of this article is to capture how the history of HT development reached Indonesia? What is the government's attitude towards HTI organizations in Indonesia? How did the